2017
DOI: 10.1590/1414-431x20176211
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling identifies miR-7-5p and miR-26b-5p as differentially expressed in hypertensive patients with left ventricular hypertrophy

Abstract: Recent evidence suggests that cell-derived circulating miRNAs may serve as biomarkers of cardiovascular diseases. However, a few studies have investigated the potential of circulating miRNAs as biomarkers for left ventricular hypertrophy (LVH). In this study, we aimed to characterize the miRNA profiles that could distinguish hypertensive patients with LHV, hypertensive patients without LVH and control subjects, and identify potential miRNAs as biomarkers of LVH. LVH was defined by left ventricular mass indexed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…These results show that miR‐22‐3p may contain important information on the onset, progression, prognosis, and other aspects in patients with cardiovascular disease. A previous study indicated that miR‐26b‐5p was upregulated in the serum of left ventricular hypertrophy (LVH) hypertensive patients compared with healthy controls . In our research, circulating miR‐26b‐5p was significantly upregulated in CAD patients.…”
Section: Discussionsupporting
confidence: 53%
“…These results show that miR‐22‐3p may contain important information on the onset, progression, prognosis, and other aspects in patients with cardiovascular disease. A previous study indicated that miR‐26b‐5p was upregulated in the serum of left ventricular hypertrophy (LVH) hypertensive patients compared with healthy controls . In our research, circulating miR‐26b‐5p was significantly upregulated in CAD patients.…”
Section: Discussionsupporting
confidence: 53%
“…However, levels of miR‐9 and miR‐126 in peripheral blood mononuclear cells (PBMCs) of hypertensive patients are reduced compared with healthy controls 178. Functionally, miR‐7‐5p can repress EC proliferation and angiogenesis by targeting RAF1,176 and let‐7 can induce oxidative stress and cell injury,177 suggesting that the up‐regulation of let‐7 may aggravate atherosclerosis, thereby modulating hypertension. In addition, miR‐9 can inhibit myocardin expression, and miR‐9 mimic can reverse the hypertrophic response and improve cardiac structure and function 179.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…Some recent studies reported that serum miR-510 is increased in hypertension patients 175 and serum miR-7-5p and miR-26b-5p are elevated in the left ventricular hypertrophy (LVH) hypertensive patients compared with healthy individuals. 176 Moreover, let-7 levels in ECs and plasma from hypertension patients are higher than those from healthy controls. 177 However, levels of miR-9 and miR-126 in peripheral blood mononuclear cells (PBMCs) of hypertensive patients are reduced compared with healthy controls.…”
Section: Hypertensionmentioning
confidence: 99%
“…For instance, elevated plasma levels of miR-29a are associated with hemolysis in patients with hypertrophic cardiomyopathy 107 . MiR-7-5p and miR-26b-5p are upregulated in the circulation of patients with left ventricular hypertensive compared with healthy subjects, which entail them as novel biomarkers for this disease 108 . Given the fact that ncRNA mimics or inhibitors can be easily synthesized and delivered to cells or organs with low toxicity 109 , ncRNAs will also be a promising and important modifiers to prevent cardiac hypertrophy.…”
Section: Future Considerationsmentioning
confidence: 99%